Tyranny of the minority : why American democracy reached the breaking point - Levitsky, Steven; Ziblatt, Daniel, 1972- (Crown, 2023)
"A call to reform our antiquated political institutions before it's too late-from the New York Times bestselling authors of How Democracies Die. America is undergoing a massive experiment: It is moving, in fits and starts, toward a multiracial democracy, something few societies have ever done. But the prospect of change has sparked an authoritarian backlash that threatens the very foundations of our political system. Why is democracy under assault here, and not in other wealthy, diversifying nations? And what can we do to save it? With the clarity and brilliance that made their first book, How Democracies Die, a global bestseller, Harvard professors Steven Levitsky and Daniel Ziblatt offer a coherent framework for understanding these volatile times. They draw on a wealth of examples-from 1930s France to present-day Thailand-to explain why and how political parties turn against democracy. They then show how our Constitution makes us uniquely vulnerable to attacks from within: It is a pernicious enabler of minority rule, allowing partisan minorities to consistently thwart and even rule over popular majorities. Most modern democracies-from Germany and Sweden to Argentina and New Zealand-have eliminated outdated institutions like elite upper chambers, indirect elections, and lifetime tenure for judges. The United States lags dangerously behind. In this revelatory book, Levitsky and Ziblatt issue an urgent call to perfect our national experiment. It's a daunting task, but we have remade our country before-most notably, after the Civil War and during the Progressive Era. And now we are at a crossroads: America will either become a multiracial democracy or cease to be a democracy at all"--